Frequency of Depressive Disorder among Patients of Breast Cancer Visiting a Tertiary Care Public Hospital at Karachi - Wadhwani, Anil Kumar; Ali, Wamiq; Jat, Muhammad Ilyas (Journal of Liaquat University of Medical & Health Sciences, 2020)
OBJECTIVE: To determine the frequency of depressive disorder in diagnosed cases of breast cancer visiting a tertiary care public hospital at Karachi. METHODOLOGY: Descriptive Cross sectional study, conducted at Department of Oncology, Jinnah Postgraduate Medical Centre, Karachi from May to November 2015. Total 93 women who fulfilled the inclusion criteria were included in the study. Brief history of breast cancer was taken and then patients were assessed for depression on the basis of Hamilton Rating Scale for depression and cut off score of ? 7 was marked as women with positive depressive disorder. Data was analyzed on SPSS version 22. RESULTS: Mean ± SD of age was 58.64±11.26 with C.I (56.32-60.95) years. Mean ± SD of duration of breast cancer and Hamilton rating score for depression were 15.86±5.26 with C.I (14.77-16.94) and 8.23±7.55 with C.I (6.67-9.78) respectively. Out of 93 women frequency of depressive disorder was found in 54 (58%) patients. CONCLUSION: The study showed that Depressive Disorder among patients of breast cancer is quite high. For managing breast cancer patients, more care or support should be given to this type of patients as they are at high risk of depression. KEY WORDS: Depressive disorder, Breast cancer, Malignancy, Frequency.